2013
DOI: 10.1186/1471-2458-13-707
|View full text |Cite
|
Sign up to set email alerts
|

Weight misperception amongst youth of a developing country: Pakistan -a cross-sectional study

Abstract: BackgroundWeight misperception is the discordance between an individual’s actual weight status and the perception of his/her weight. It is a common problem in the youth population as enumerated by many international studies. However data from Pakistan in this area is deficient.MethodsA multi-center cross-sectional survey was carried out in undergraduate university students of Karachi between the ages of 15–24. Participants were questioned regarding their perception of being thin, normal or fat and it was compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
4
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 23 publications
4
23
4
2
Order By: Relevance
“…Innovative interventions may be needed to address young men to take the problem more seriously [6]. Contrary to some other studies [8,12,13], this study did not find any association between older age, lower socioeconomic status and underestimation of overweight. This may be explained by the study population of university students being a rather homogeneous group, with young age and coming generally from a higher socioeconomic background.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Innovative interventions may be needed to address young men to take the problem more seriously [6]. Contrary to some other studies [8,12,13], this study did not find any association between older age, lower socioeconomic status and underestimation of overweight. This may be explained by the study population of university students being a rather homogeneous group, with young age and coming generally from a higher socioeconomic background.…”
Section: Discussioncontrasting
confidence: 84%
“…Men had a greater underestimation of their overweight status than women. This finding is confirmed in other studies [4,12,13], and may be because males prefer slightly heavier build [36]. Generally, in a review, Cohane [37] found that girls typically wanted to be thinner, while boys frequently wanted to be bigger.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…As well as being prevalent among adults, underestimation of self‐perceived weight status is common among children and adolescents 19, 20, 21, with a recent study of more than 70,000 US high school students showing that around one third of the respondents with overweight or obesity failed to correctly identify their weight status as being overweight 22. Underestimation of weight status among individuals with overweight and obesity is frequently observed in both the rich and the poor 23, 24, 25, as well as across a diverse range of ethnic groups 9, 26, 27.…”
Section: Underestimation Of Self‐perceived Weight Statusmentioning
confidence: 99%
“…The physicians recognize obesity as a rising problem in Pakistan, but they do not possess knowledge regarding its complexities neither are significantly trained to treat it successfully. They are hardly trained on acquiring counseling skills related to diet, nutrition, and healthy lifestyles [39]. Similarly, the role of nutritionists and community pharmacist in obesity management is not well perceived by the community as well as by different stakeholders.…”
Section: Overview Of Obesity Management In Pakistanmentioning
confidence: 99%